2019
DOI: 10.1002/cmdc.201900544
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity Relationships of Cinnamate Ester Analogues as Potent Antiprotozoal Agents

Abstract: Protozoal infections are still a global health problem, threatening the lives of millions of people around the world, mainly in impoverished tropical and sub‐tropical regions. Thus, in view of the lack of efficient therapies and increasing resistances against existing drugs, this study describes the antiprotozoal potential of synthetic cinnamate ester analogues and their structure‐activity relationships. In general, Leishmania donovani and Trypanosoma brucei were quite susceptible to the compounds in a structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 48 publications
3
37
0
Order By: Relevance
“…Those bits from the MACCS fingerprint would be likely responsible for the activity. Such features are related to the number of oxygen atoms in the molecule and to the existence of linear alkyl chains, which is in perfect agreement with the previously published qualitative SAR results [25], but also led to inferring that the antileishmanial activity is overall affected by changes in polarity. The same analysis for the antitrypanosomal activity-based model (Figure 2C) indicated that the most important keys in that case are 54, 131, 127, and 72 (Figure 2E), which are mainly related to the presence of geminal oxygens (i.e., carboxyl, nitro, etc.)…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Those bits from the MACCS fingerprint would be likely responsible for the activity. Such features are related to the number of oxygen atoms in the molecule and to the existence of linear alkyl chains, which is in perfect agreement with the previously published qualitative SAR results [25], but also led to inferring that the antileishmanial activity is overall affected by changes in polarity. The same analysis for the antitrypanosomal activity-based model (Figure 2C) indicated that the most important keys in that case are 54, 131, 127, and 72 (Figure 2E), which are mainly related to the presence of geminal oxygens (i.e., carboxyl, nitro, etc.)…”
Section: Resultssupporting
confidence: 89%
“…The noteworthy antileishmanial and antitrypanosomal activity of various cinnamate ester analogues among compounds 1 – 34 , in addition to the outstanding selectivity of some of those compounds against the parasites under study in comparison with mammalian cells [25], encouraged the detailed QSAR study presented here. A new set of scoring functions was defined to help selecting the best models within large model populations obtained by GA/MLR with very similar statistical validation parameters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Butyl p -coumarate ( 6 ) being compared to compound 1 , presented the lowest leishmanicidal potency, with an EC 50 of 323.29 ± 50.04 μg/mL. Interestingly, Bernal et al (2019) [ 49 ] found that groups with a medium length linear alkyl chain exhibited higher activity against L. donovani when compared to groups presenting short chains [ 50 ]. Meanwhile, pentyl p -coumarate ( 7 ) was five times less potent than isopentyl p -coumarate ( 8 ) (32.03 ± 5.054.3 μg/mL, 6.02 ± 0.22 μg/mL, respectively), possibly due to compound 8 branching.…”
Section: Resultsmentioning
confidence: 99%